Testing and measurement- An overview / Jagdip Kaur - Kaur, Jagdip (Universiti Teknologi MARA Cawangan Pahang, 1990)
How often we question the proper functioning of the bathroom scale when it gives a higher reading than we expect? How frequently we challenge the accuracy of the speed gun when we are stopped for a speeding violation? These two questions reflect how often all of us question most of the measures we encounter in the aspects of our daily lives, particularly whenever they yield results inconsistent with our hopes or expectations. But when achievement test results turn out to be lower than expected, the critical finger rarely is pointed first at the tests themselves.